Research of the effectiveness of ‘a day with client’ in UiTM Samarahan campus from the perspective of customers/ Catherin Rantai… [et.al.] - Rantai, Catherin; Edward Jawa, Jennifer; Mohamad, Faridah; Sibi, Noryati; Ali, Anika (2004)
The purpose of this research is to measures the effectiveness of “A Day with Client” program from customer perspective in UiTMCS. Besides, the purpose of the research is also to make analysis what are the causes of the effectiveness or ineffectiveness of the program. Methodology that been used is by distributing questionnaire to 80 respondents. Here, we distribute the analysis questionnaire by using random sampling method. The scope of our research is including academic staff, non- academic staff and students of UiTMCS.